The Effect Of Green Intellectual Capital, CEO Characteristic, Free Cash Flow On Prudence Moderated By Enviromental Performance - Whittleliang Hakki, tandry; Herlina, Herlina; Akwila, Karvicha; Jurjanta, Priccilya (DINASTI RESEARCH, 2024)
The rapid development of many industries in the world has resulted in environmental damage due to excessive use and exploitation of natural resources. As a result, there is a decline in environmental quality resulting in global warming, ozone depletion, pollution, and acid rain. The impact of environmental conventions in the world Montreal Convention, Kyoto Protocol, Ban on the Use of Certain Hazardous Materials and increasing consumer environmentalism can change the context of competition in industries around the world. This study aims to examine the effect of Green Intellectual Capital, CEO Characteristic, Free Cash Flow on Prudence moderated by Environmental Performance. This study took the research population in the energy sector companies listed on the Indonesia Stock Exchange for the period 2019-2023. The type of data used in this study is secondary data in the form of financial reports of companies that are used as samples. The research method used in this study is a quantitative research method. The sample was selected using the purposive sampling method. For hypothesis testing, this study uses multiple linear regression analysis. Based on the results of this study, it shows that Green Intellectual Capital, Busy Director, and Free Cash Flow have an effect on prudence but CEO Tenure has no effect on Prudence. Environmental Performance strengthens the influence of Green Intellectual Capital, Busy Director, and Free Cash Flow on prudence and Environmental Performance strengthens the influence of CEO Tenure on prudence.